2010
DOI: 10.1007/s11095-010-0123-9
|View full text |Cite
|
Sign up to set email alerts
|

Microneedle-Based Intradermal Delivery Enables Rapid Lymphatic Uptake and Distribution of Protein Drugs

Abstract: Microneedle delivery is applicable to a wide variety of protein drugs and is capable of effective parenteral administration of therapeutic drug dosages. This delivery route alters absorption kinetics via targeting a tissue bed better perfused with lymphatic and blood vessels than the SC space. Microneedle delivery may afford various advantages, including a robust method to increase the absorption rate and bioavailability of proteins that have been challenging to deliver at therapeutic levels or with physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(90 citation statements)
references
References 45 publications
1
88
0
1
Order By: Relevance
“…The matrix of MNs was made from cross-linked HA to improve the stiffness of MNs and restrict the loss of GRVs from needles. With transcutaneous administration, the GRVs loaded in MNs disassembled when exposed to high interstitial fluid glucose in vascular and lymph capillary networks (35), thereby promoting the release of insulin, which was then taken up quickly through the regional lymph and capillary vessels (36). We demonstrated that this "smart insulin patch" with a novel glucoseresponsive mechanism displayed rapid responsiveness for glucose regulation and reliable avoidance of hypoglycemia in a mouse model of type 1 diabetes.…”
Section: Significancementioning
confidence: 96%
“…The matrix of MNs was made from cross-linked HA to improve the stiffness of MNs and restrict the loss of GRVs from needles. With transcutaneous administration, the GRVs loaded in MNs disassembled when exposed to high interstitial fluid glucose in vascular and lymph capillary networks (35), thereby promoting the release of insulin, which was then taken up quickly through the regional lymph and capillary vessels (36). We demonstrated that this "smart insulin patch" with a novel glucoseresponsive mechanism displayed rapid responsiveness for glucose regulation and reliable avoidance of hypoglycemia in a mouse model of type 1 diabetes.…”
Section: Significancementioning
confidence: 96%
“…In the case of lymphedema, in particular, a major limitation in the development of new treatments has been the lack of in vivo imaging diagnostics capable of quantifying differences in the dynamic pump function of lymphatic vessels in real time. 3 Recently, the lymphatic system has garnered increased interest, as its roles in tumor metastasis, 4 dermal drug delivery, 5 chronic inflammation, 6 and lipid transport 7 are beginning to be appreciated. With the new understanding of the role of lymphatic vessels in disease processes and therapies, there is now a greater need for major advances in the diagnostic imaging tools available to adequately visualize and quantify lymphatic pump function.…”
Section: Introductionmentioning
confidence: 99%
“…10,53 The drugs can be subsequently absorbed into the blood stream or lymphatic circulation. 11,54 It is expected that the protein released will accumulate in the subepidermal tissues and be rapidly absorbed from the highly vascularized regions lying underneath.…”
Section: In Vitro Release Of Bsa From Microneedlesmentioning
confidence: 99%